2013
DOI: 10.1093/aob/mct278
|View full text |Cite
|
Sign up to set email alerts
|

Inflorescence dimorphism, heterodichogamy and thrips pollination in Platycarya strobilacea (Juglandaceae)

Abstract: Background and AimsUnlike other taxa in Juglandaceae or in closely related families, which are anemophilous, Platycarya strobilacea has been suggested to be entomophilous. In Juglandaceae, Juglans and Carya show heterodichogamy, a reproductive strategy in which two morphs coexist in a population and undergo synchronous reciprocal sex changes. However, there has been no study focusing on heterodichogamy in the other six or seven genera, including Platycarya.MethodsInflorescence architecture, sexual expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 43 publications
1
26
0
1
Order By: Relevance
“…We found that unisexuality is a temporary trait based on the reduction of the ratio of M and F types with the maturation of the stand (Table 2). Similar findings were reported in J. ailanthifolia and J. mandshurica [9,29]. Researchers believe that the unisexual trait (F and/or M) is an environmental and/or nutrient (young age) response phenotype rather than a separate morph [9,24,25].…”
Section: Morph Ratio and Transitionsupporting
confidence: 69%
See 3 more Smart Citations
“…We found that unisexuality is a temporary trait based on the reduction of the ratio of M and F types with the maturation of the stand (Table 2). Similar findings were reported in J. ailanthifolia and J. mandshurica [9,29]. Researchers believe that the unisexual trait (F and/or M) is an environmental and/or nutrient (young age) response phenotype rather than a separate morph [9,24,25].…”
Section: Morph Ratio and Transitionsupporting
confidence: 69%
“…Labile sex expression was documented in some heterodichogamous trees across years, like in Acer pseudoplatanus [24,28]. It is reported that the sexual phenotype changed mainly from unisexual to the monoecious type, with few or no changes between PA and PG [8,9]. We found that unisexuality is a temporary trait based on the reduction of the ratio of M and F types with the maturation of the stand (Table 2).…”
Section: Morph Ratio and Transitionmentioning
confidence: 55%
See 2 more Smart Citations
“…A maioria destas espécies documentadas é economicamente visada ou amplamente cultivada, cenário este que facilita a detecção desta forma de dimorfismo. A dificuldade no estudo para verificar a mudança sexual em populações de plantas dimórficas, que requerem monitoramento em longo prazo, além da mudança de sexo poder variar muito em tempo ocorrendo do dia para a noite ou uma única vez durante todo o período de floração, evidencia a necessidade de mais estudos sobre os sistemas sexuais de populações que apresentam variações funcionais nos sistemas reprodutivos (Renner 2001;Renner et al 2007;Wang et al 2012;Fukuhara & Tokumaru 2013). Estudos com essas abordagens devem ser realizados com espécies de Simaba.…”
Section: Eckhart 1999)unclassified